The relationship between serum hypoxia-inducible factor 1α and coronary artery calcification in asymptomatic type 2 diabetic patients - Li, Gang; Lu, Wei-hua; Ai, Rong; Yang, Jian-hong; Chen, Fang; Tang, Zhong-zhi (Cardiovascular diabetology, 2014)
Hypoxia-inducible factor 1 (HIF-1), a master regulator of oxygen homeostasis, is a heterodimer consisting of HIF-1α and HIF-1β subunits, and is implicated in calcification of cartilage and vasculature. The goal of this study was to determine the relationship between serum HIF-1α with coronary artery calcification (CAC) in patients with type 2 diabetes. The subjects were 405 (262 males, 143 females, age 51.3 ± 6.4 years) asymptomatic patients with type 2 diabetes mellitus. Serum HIF-1α and interleukin-6 (IL-6) levels were measured by ELISA. CAC scores were assessed by a 320-slice CT scanner. The subjects were divided into 4 quartiles depending on serum HIF-1α levels. Average serum HIF-1α was 184.4 ± 66.7 pg/ml. Among patients with higher CAC scores, HIF-1α levels were also significantly increased (p <0.001). HIF-1α levels positively correlated with CRP, IL-6, UKPDS risk score, HbA1c, FBG, and CACS, but did not correlate with diabetes duration, age, and LDL. According to the multivariate analysis, HIF-1α levels significantly and independently predict the presence of CAC. ROC curve analysis showed that the serum HIF-1α level can predict the extent of CAC, but the specificity was lower than the traditional risk factors UKPDS and HbA1c. As a marker of hypoxia, serum HIF-1α level may be an independent risk factor for the presence of CAC. These findings indicate that elevated serum HIF-1α may be involved in vascular calcification in patients with type 2 diabetes mellitus.